Effect of Addition of Fermented Liquid on Silage Quality of Turi Leaves (Sesbania grandiflora) and Cassava Tubers (Manihot esculenta) as Fish Feed Ingredients - Daniel Wyclif Maatuil; Jacob L. A. Uktolseja; Desti Christian Cahyaningrum (Jurnal Biologi Tropis, 2021)
Utilization of Turi leaves (Sesbania grandiflora) and cassava tubers (Manihot esculenta) as a protein source to replace some fish meal can be done by silage of the two ingredients. This silage fermentation process requires adding inoculum from the fermented liquid to obtain good quality silage. This study aims to determine the effect of fermented liquid on the quality of silage made from Turi leaves and cassava tubers for fish feed ingredients through parameters of Titration End Point and pH levels. The research treatment was the addition of fermented liquid for four days with a sugar content of 1% (CT4-1%) in the treatment silage (S_CT4-1%), compared to the initial silage (SA) and the negative control silage (SKN). The results showed a significant (P<0.05) addition of CT4-1% fermented liquid, namely Titration End Point S_CT4-1% a significant increase of 281.9% from 18.33 mL in SA to 70.00 mL in treatment. The pH condition significantly decreased from 5.35 in SA to 4.17 in the treatment. Titration End Point on SKN only increased by 90.9% from 18.33 mL to 35.00 mL, with pH only dropping from 5.35 to 4.31. Study concuded that CT4-1% produced excellent quality silage of Turi leaves and cassava tubers based on TAT and pH levels. This quality can increase the chance of silage of Turi leaves and cassava tubers treated with CT4-1% as a partial substitute for fish meal in fish feed manufacture.